Conserved Odorant-Binding Proteins from Aphids and Eavesdropping Predators - Vandermoten, Sophie; Francis, Frédéric; Haubruge, Eric; Leal, Walter S. (PLOS ONE, 2011)
Background The sesquiterpene (E)-ß-farnesene is the main component of the alarm pheromone system of various aphid species studied to date, including the English grain aphid, Sitobion avenae. Aphid natural enemies, such as the marmalade hoverfly Episyrphus balteatus and the multicolored Asian lady beetle Harmonia axyridis, eavesdrop on aphid chemical communication and utilize (E)-ß-farnesene as a kairomone to localize their immediate or offspring preys. These aphid-predator systems are important models to study how the olfactory systems of distant insect taxa process the same chemical signal. We postulated that odorant-binding proteins (OBPs), which are highly expressed in insect olfactory tissues and involved in the first step of odorant reception, have conserved regions involved in binding (E)-ß-farnesene. Methodology We cloned OBP genes from the English grain aphid and two major predators of this aphid species. We then expressed these proteins and compare their binding affinities to the alarm pheromone/kairomone. By using a fluorescence reporter, we tested binding of (E)-ß-farnesene and other electrophysiologically and behaviorally active compounds, including a green leaf volatile attractant. Conclusion We found that OBPs from disparate taxa of aphids and their predators are highly conserved proteins, with apparently no orthologue genes in other insect species. Properly folded, recombinant proteins from the English grain aphid, SaveOBP3, and the marmalade hoverfly, EbalOBP3, specifically bind (E)-ß-farnesene with apparent high affinity. For the first time we have demonstrated that insect species belonging to distinct Orders have conserved OBPs, which specifically bind a common semiochemical and has no binding affinity for related compounds.